Longitudinal Study of Thyroid Hormones between Conventional and Organic Farmers in Thailand - Nankongnab, Noppanun (Toxics, 2020)
Many pesticides are endocrine-disrupting chemicals that can interfere with hormone levels. This study aimed to assess the longitudinal impact of exposure to pesticides on thyroid hormone levels, including Thyroid Stimulating Hormone (TSH), Free Triiodothyronine (FT3), Free Thyroxine (FT4), Triiodothyronine (T3), and Thyroxine (T4). Both conventional (i.e., pesticide using) and organic farmers were interviewed using questionnaires, and blood samples were collected at 7–9 a.m. to determine thyroid hormone levels for four rounds, with a duration of eight months between each round. A linear mixed model of the natural log of the individual hormone levels used random intercepts for subjects while controlling gender, baseline age, and body mass index (BMI) was used to compare between conventional and organic farmers or the impact of cumulative days of spraying insecticides, herbicides or fungicides. The estimated marginal means of the thyroid hormone levels (TSH, FT3, T3, and T4) estimated from the linear mixed models were significantly higher among the conventional farmers than organic farmers. As cumulative spray days of insecticide, herbicide or fungicide increased, TSH and FT3 increased significantly. FT4 decreased significantly as cumulative spray days of insecticide or fungicide increased. These findings suggest that the insecticides, herbicides, and fungicides sprayed by conventional farmers exert endocrine-disrupting activities, altering the hypothalamic-pituitary-thyroid (HPT) axis homeostasis.